Analysis of Student Response to the Use of Biochemistry e-Module on Carbohydrate Materials in Enhanching Learning Independence - Mairisiska, Titin; Ramadani, Ramadani; Qadariah, Nosi (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to analyze student responses to the use of a biochemistry e-module on carbohydrate material and its impact on learning independence. This quantitative descriptive research involved 40 students from the Biology and Chemistry study programs who had used the e-module. Data were collected through a questionnaire covering five indicators: ease of use, effectiveness of material delivery, level of interactivity, learning independence, and general response. The results showed that for the ease of use indicator, the carbohydrate e-module received an average response of "very good" with an average percentage of 83%. The effectiveness of material delivery scored 82.75%, while the level of interactivity reached 85.7%. However, the learning independence indicator had a lower average score (78.7%), indicating the need to strengthen self-learning motivation and encourage further exploration of additional information. The study concludes that the biochemistry e-module on carbohydrate material is effective in enhancing students' understanding but requires some improvements, such as adding a glossary feature and interactive elements to optimally support learning independence. The integration of technology in learning is expected to continue developing to improve the effectiveness of science-based education.